Ethical Leadership and Servant Leadership on Team Creativity: Task Interdependencies as a Moderating Role - Cheng-Wen Lee; Adil Zareef Khan (International Journal of Business and Economic Affairs, 2024)
The research investigates the impact of ethical leadership and servant leadership on team innovation while testing task interdependence’s moderating role. Data was gathered from 243 participants employed in construction sector companies in Islamabad, Rawalpindi, and Muzaffarabad, Pakistan, to examine the suggested connections. This was done through the use of structured and self-administered questionnaires. The acquired data were analyzed using correlation and regression analysis in the statistical package for social sciences (SPSS). The findings indicated that both ethical and Servant Leadership have a significant and beneficial influence on team creativity.Furthermore, the suggested moderating assumptions about task interdependence were also confirmed. The discussion encompasses the study’s consequences regarding theory and practical applications. The study also analyzed its research constraints and identified potential areas for further investigation.